Antimicrobial Resistance and Plasmid Profiling of ESBL Producing Klebsiella spp. of Bovine Origin of Eastern Plain Zone of Uttar Pradesh - Yadav, Vibha; Joshi, Rajesh Kumar; Singh, Satyavrat; Maurya, Satyendra Kumar; Niyogi, Debasish; Shrivastva, Dharam Prakash; Yadav, Deepak (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Emergence of antimicrobial resistance in animal husbandry is of utmost concern as it has resulted in therapeutic failure and nowadays it is one of the latest challenges faced by scientific community across the world. Extensive use of antibiotics without performing antibiotic susceptibility testing may lead to development of multidrug resistant (MDR) organisms. This study was undertaken to assess the AMR pattern and their correlation with plasmid profiling in ESBL producing Klebsiella spp. from bovine origin. Total 160 samples were collected from 2 district of Eastern Plain Zone of Uttar Pradesh (India) and 63 (39.37%) isolates were confirmed as Klebsiella spp. by conventional methods (cultural characteristics on selective media & biochemical tests). Antimicrobial susceptibility testing of confirmed isolates revealed 82.0%-94.0% resistance to 3rd & 4th generation cephalosporin, 100% to ampicillin and all isolates were found 100% sensitive to aminoglycosides, chloramphenicol and polypeptides class of antibiotics. Total 49 (77.8%) isolates were confirmed as ESBL producers using DDST and ESBL E-strip test, out of which 45 (71.43%) isolates revealed the presence of bla-CTX-M gp genes by PCR analysis. On plasmid profiling, total 82.82% isolates revealed the presence of plasmid with molecular weight between 2.5 kb to >10 kb and number 1-2. These high molecular weight plasmids are mostly situated on conjugative plasmid, which are horizontally transferred from one species to another in highly populous country like India.
Keywords: Bovine; ESBLs; Klebsiella spp; MDR; Plasmid